Configuring robust DNA strand displacement reactions for in situ molecular analyses - Duose, Dzifa Y. (Oxford University Press, 2012)
The number of distinct biomolecules that can be visualized within individual cells and tissue sections via fluorescence microscopy is limited by the spectral overlap of the fluorescent dye molecules that are coupled permanently to their targets. This issue prohibits characterization of important functional relationships between different molecular pathway components in cells. Yet, recent improved understandings of DNA strand displacement reactions now provides opportunities to create programmable labeling and detection approaches that operate through controlled transient interactions between different dynamic DNA complexes. We examined whether erasable molecular imaging probes could be created that harness this mechanism to couple and then remove fluorophore-bearing oligonucleotides to and from DNA-tagged protein markers within fixed cell samples. We show that the efficiency of marker erasing via strand displacement can be limited by non-toehold mediated stand exchange processes that lower the rates that fluorophore-bearing strands diffuse out of cells. Two probe constructions are described that avoid this problem and allow efficient fluorophore removal from their targets. With these modifications, we show one can at least double the number of proteins that can be visualized on the same cells via reiterative in situ labeling and erasing of markers on cells.